The hepatocyte insulin receptor is required to program the liver clock and rhythmic gene expression - Fougeray, Tiffany (2023)
Liver physiology is circadian and sensitive to feeding and insulin. Food intake regulates insulin secretion and is a dominant signal for the liver clock. However, how much insulin contributes to the effect of feeding on the liver clock and rhythmic gene expression remains to be investigated. Insulin action partly depends on changes in insulin receptor (IR)-dependent gene expression. Here, we use hepatocyte-restricted gene deletion of IR to evaluate its role in the regulation and oscillation of gene expression as well as in the programming of the circadian clock in the adult mouse liver. We find that, in the absence of IR, the rhythmicity of core-clock gene expression is altered in response to day-restricted feeding. This change in core-clock gene expression is associated with defective reprogramming of liver gene expression. Our data show that an intact hepatocyte insulin receptor is required to program the liver clock and associated rhythmic gene expression.